2001
DOI: 10.1038/sj.gt.3301351
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine/DNA complexes shielded by transferrin target gene expression to tumors after systemic application

Abstract: Systemic application of positively charged polycation/DNA complexes has been shown to result in predominant gene expression in the lungs. Targeting gene expression to other sites, eg distant tumors, is hampered by nonspecific interactions largely due to the positive surface charge of transfection complexes. In the present study we show that the positive surface charge of PEI (25 kDa branched or 22 kDa linear)/DNA complexes can be efficiently shielded by covalently incorporating transferrin at sufficiently high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
237
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 331 publications
(257 citation statements)
references
References 44 publications
15
237
0
Order By: Relevance
“…With increasing N/P ratios even marked fetal mortality was observed, most probably caused by embolic events either in the livers or lungs of the injected animals because of the high electropositivity of the complexes leading to aggregation with blood components. 15 According to our results, linear PEI22 is better suited for in utero application than the branched forms of the polycation (PEI800 or PEI25). Best in vivo results were obtained with ligand-free PEI22/DNA complexes generated in the presence of salt.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…With increasing N/P ratios even marked fetal mortality was observed, most probably caused by embolic events either in the livers or lungs of the injected animals because of the high electropositivity of the complexes leading to aggregation with blood components. 15 According to our results, linear PEI22 is better suited for in utero application than the branched forms of the polycation (PEI800 or PEI25). Best in vivo results were obtained with ligand-free PEI22/DNA complexes generated in the presence of salt.…”
Section: Discussionmentioning
confidence: 61%
“…This was surprising, since incorporation of the ligand into the complexes had previously been shown to be beneficial for postnatal in vivo approaches. 15 Previous reports have described much higher reporter gene expression in adult mouse lungs with salt-free PEI22/DNA complexes as compared to salt-containing formulations. 18,19 This was confirmed in our study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An exception to this is delivery to the lung, where it has been shown that large aggregating PEI/DNA particles passively target the lung following tail-vein injection. 23,24 For receptor-specific endocytosis, ligands such as epidermal growth factor (EGF) 25 and RGD peptide 26 have been utilized to increase cell specificity and overall uptake in vitro and in vivo. Though targeting often increases transfection, some experiments show that uptake that is both specific and efficient only occurs at a narrow window of charge ratios or not at all.…”
Section: Designing Polymeric Nanoparticles For Increased Uptake and Lmentioning
confidence: 99%